PENGARUH IMPLEMENTASI PROGRAM KELUARGA HARAPAN TERHADAP KESEJAHTERAAN MASYARAKAT DI KELURAHAN KINILOW KECAMATAN TOMOHON UTARA KOTA TOMOHON - SITORUS, GABRIELLA KRISTIANY; RARES, JOYCE; PLANGITEN, NOVVA (Sam Ratulangi University, 2020)
This research is motivated by the most prominent problem in Indonesia, namely poverty. One waythat the Indonesian government has done to reduce the problem of poverty is to provide assistance to thepoor, commonly referred to as social assistance or social assistance. Social Assistance is a transfer ofmoney or goods given to the community to protect against the possibility of social risks and to improve thewelfare of the community. To minimize the problems of social welfare, especially poverty, the Governmentof Indonesia has various prevention programs, one of which is a social assistance based program, theFamily Hope Program (PKH). Tomohon City is one of the cities in Indonesia that was targeted by theprogram. The method used in this research is quantitative method. While the instruments and datacollection techniques are interviews and questionnaires. Then, the analysis technique used is simple linearregression analysis to test the effect between variables. Based on research carried out and continued byanalyzing the data obtained, that the implementation of the family hope program has an influence on thewelfare of the community in Kinilow Village, Tomohon Utara District, Tomohon City.Keywords: Program Implementation, Community Welfare